PENGARUH KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DINAS PERIKANAN KABUPATEN KARO - Menanti Sembiring; Rikawati Ginting Munthe; Sriwahyuni Br Tarigan (JURNAL AGROTEKNOSAINS, 2022)
Job satisfaction is closely related to employee performance. This study aims to determine the effect of job satisfaction on the performance of the employees of the Karo Regency Fisheries Service. The sample in this study is a saturated sample so that all employees of the Karo Regency Fisheries Service as many as 37 people become subjects. Data were analyzed by simple linear regression analysis. Based on the calculations obtained the results of a simple linear regression equation; Y = 9.414+0.736X+e and the value of tcount = 9.206 while the value of ttable = 2.030 with a significance of 0.000 <0.05 or the value of tcount > ttable (9.206 > 2.030), meaning that job satisfaction z is 0.708. which means that 70.80% employee performance is influenced by job satisfaction and 29.20% can be explained by other variables outside this research model.